Concept of «Mystery» and its Realization in the Works of J. Lippard and N. Buntline - V. V. Bezrukova; A. V. Garkusha (Дискурс, 2024)
Introduction. The article is devoted to the analysis of the linguistic means expressing the concept of «mystery» in the fictional works of J. Lippard and N. Buntline, the allocation of its socio-cultural component and the field model construction of lexical units representing this concept. The relevance of the research is due to the interest of modern linguistics in the study of the conceptual sphere of artistic works of the «urban mysteries» genre by American authors.Methodology and sources. The study was conducted within the framework of a linguistic and cultural approach using methods of description, comparison, interpretative analysis, conceptual analysis, the method of dictionary definitions analyzing, structural and semantic analysis, and the method of quantitative calculations. The illustrative material of the study consisted of more than 74 lexical units representing the «mystery» concept in the language, 45 of which were found in the analyzed works. The material was obtained by the method of directed sampling from the fictional works of American authors of the 19th century.Results and discussion. This article discusses and analyzes various interpretations of the concept of «mystery» by domestic and foreign scientists; defines the role of the concept in the work of fiction as a whole and in the analyzed novels of two authors J.  lippard and N. Buntline; identifies the features of the linguistic implementation of the «mystery» concept; classifies the linguistic units of the concept according to their parts of speech, semantics and stylistic coloring; analyzes the writers’ linguistic pictures of the world and the conceptual sphere of their works, the illustrative zone of which reveals the reasons for the similarity not only of the storylines of the works, but also of their lexical content.Conclusion. The study made it possible to describe and illustrate the individual style of American authors of the 19th century through a system of expressive means that correlates the inner world of the writer with the artistic reality, the artistic world of the text created by the «poetic» language. The mental world can be interpreted in cognitive terminology as an individual poetic conceptual sphere, or the conceptual system of the author, consisting of a conceptual, objective, associative, figurative and symbolic layer of the concept. The study showed that the learning of the writer's linguistic picture of the world and the conceptual sphere of the work can be carried out using a field model, analyzing the LSF forming the «mystery» concept. The analyzed LSF is distinguished by a more specific vocabulary composition, the complication of the seme structure of words, the seme expansion and the restructuring of their hierarchy, which together form the artistic worldview of the authors.